Pengembangan Sistem Pemantauan dan Peringatan Dini Parameter Lingkungan Mikro dalam Rumah Kaca Berdasarkan Pendekatan Logika Fuzzy Berbasis Teknologi Short Message Services (SMS) - Mohamad Solahudin; Rena Nurista (PERTETA, 2009)
Farmers in the tropics also has many cultivated plants in the greenhouse. Excess plants cultivated inthe greenhouse produced plants will look cleaner because the dirt and protected from rain water. Plantgrowth will be faster because the micro environmental conditions in a greenhouse can be controlled and theplants will be protected from pests and diseases. Failure due to an automatic system caused by the electricsource, or non-functioning of a particular sensor equipment will result in the cultivation process controlbecomes disrupted. It required a system capable of monitoring several parameters of the greenhousein order to be anticipating a quick action to ensure the cultivation process goes smoothly. The objectiveof this research was to develop monitoring systems and early warning microenvironment parametersof plants in the greenhouse by fuzzy logic approach and short messaging services (SMS) technologybased.SMS technology was selected because it was available in all type mobile phone, easy to use,equitable access network in Indonesia, and low operational costs. The average value of the accuracy of thetemperature parameters using training data was 96.17% and using validation data was 96.75%, while thehumidity parameters using training data obtained by an average of 92.96% and using validation data was94.06%. Long service to deliver message in monitoring system between same mobile phone operator forthe temperature parameters was 32.30 seconds, and for humidity was 30.32 seconds, while the averageservice early warning system parameters was 12.96 seconds for temperature and for humidity was 13:22seconds. These results were much better than previous studies which have an average service time 2minutes.Keywords: SMS, fuzzy logic, greenhouse, early warning systemDiterima: 14 April 2009; Disetujui: 25 Ahustus 2009